Surgical repair of candida mycotic pseudoaneurysm with extensive vegetations of the ascending aorta and pulmonary artery after heart and kidney transplant. Issue 12 (28th September 2020) - Castro, Rebecca; Kai, Masashi; Ohira, Suguru; Spielvogel, David; Gass, Alan
Abstract: We report a case of invasive candidiasis causing a mycotic pseudoaneurysm involving the ascending aorta and pulmonary artery. The patient presented two years after heart‐kidney transplant with acute limb ischemia resulting from embolization of fungal vegetations. Operative findings included a pseudoaneurysm resulting from near‐complete dehiscence of the aortic suture line, and large vegetations within the ascending aorta extended to the aortic arch and pulmonary artery, with localized dehiscence of the pulmonic suture line. The ascending aorta was replaced, and the pulmonary artery was repaired with bovine pericardium. The patient did well, and blood cultures were negative at 6 months follow‐up.